2021
DOI: 10.1080/21655979.2021.1940611
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA LINC00511 regulates the expression of microRNA-625-5p and activates signal transducers and activators of transcription 3 (STAT3) to accelerate the progression of gastric cancer

Abstract: This study aimed to investigate the expression, biological function, and downstream mechanism of LINC00511 in gastric cancer (GC). In paired GC samples, LINC00511, miR-625-5p and STAT3 mRNA expression levels were detected by quantitative real-time polymerase chain reaction (qRT-PCR); STAT3 protein expression was detected by immunohistochemical (IHC). The gain-of-function and loss-of-function models were established, and the proliferative and migrative ability of GC cells were measured by CCK-8 and transwell as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Subsequently, membranes were incubated with secondary antibody (Abcam). Protein bands were visualized by an enhanced chemiluminescent kit (Applygen) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, membranes were incubated with secondary antibody (Abcam). Protein bands were visualized by an enhanced chemiluminescent kit (Applygen) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“… 77 , 78 , 79 In addition, some lncRNAs, such as HOXD-AS1, TRPM2-AS, and LINC00691, have been reported to regulate the expression of key components in the STAT3 signaling pathway. 80 , 104 , 105 …”
Section: Roles Of Lncrnas In Gcmentioning
confidence: 99%
“…In gastric cancer (GC), LINC00511 was highly expressed and further studies found LINC00511 to recruit EZH2 (enhancer of zeste 2 polycomb repressive complex 2 subunit) to the PTEN (phosphatase and tensin homolog) promoter, facilitating its methylation, and subsequently activating the PI3K/AKT pathway, promoting GC cell proliferation, migration, and stemness, while inhibiting GC cell apoptosis [ 32 ]. LINC00511 was also found to regulate the expression of microRNA-625-5p and activate signal transducers and activators of transcription 3 (STAT3) to accelerate the progression of GC [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer (CRC), the overexpression of LINC00511 accelerated CRC development by facilitating cell proliferation, metastasis, and stemness. Studies found that LINC00511 acted as a competing endogenous RNA (ceRNA) with NFIA (Nuclear Factor I A) to bind with miR-29c-3p, revealing the LINC00511/miR-29c-3p/NFIA axis as potential therapeutic targets for CRC treatment [ 33 , 34 ]. In a study on temozolomide (TMZ), the first-line chemotherapy drug for glioblastoma (GBM), LINC00511 expression upregulation correlated with the poor prognosis of GBM patients and LINC00511 silencing impaired the tolerance of TMZ, while its overexpression increased the TMZ resistance of sensitive GBM cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%